2019
DOI: 10.1007/s12325-019-01092-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Vortioxetine in the Chinese Population

Abstract: IntroductionMajor depressive disorder (MDD) is associated with a significant burden of disease in China. Awareness and better access to treatments could help alleviate the burden associated with MDD. Because variations have been observed in the pharmacokinetics (PK) of antidepressants across different races and ethnicities, evaluation of the clinical pharmacology of vortioxetine in diverse populations remains important to assess the potential need for dose adjustments.MethodsData were pooled from two phase I o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Factors such as age, sex, race/ethnicity, body weight, and liver or kidney impairment had no clinically significant effects on vortioxetine exposure (23). For example, no clinically meaningful difference in the pharmacokinetics of vortioxetine was observed between the data obtained from a study conducted in the Chinese population and previous data of a non-Chinese population (24).…”
Section: Editorialmentioning
confidence: 83%
“…Factors such as age, sex, race/ethnicity, body weight, and liver or kidney impairment had no clinically significant effects on vortioxetine exposure (23). For example, no clinically meaningful difference in the pharmacokinetics of vortioxetine was observed between the data obtained from a study conducted in the Chinese population and previous data of a non-Chinese population (24).…”
Section: Editorialmentioning
confidence: 83%
“…In a previous study, the maximal plasma concentration following multiple doses of 5, 10, or 20 mg was estimated to be 9 (0.024 μM), 18 (0.047 μM), and 33 ng/mL (0.087 μM) [ 57 ]. Other reports demonstrated that maximal plasma level following the VOR administration could reach 50 ng/mL (0.13 μM) [ 49 , 58 ]. Those values tend to be lower than the IC 50 or K D value for VOR-mediated inhibition of I K(DR) described herein.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic properties of VO have been studied in mice, rats, dogs, and in human subjects. 30 , 112 116 …”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The pharmacokinetic properties of VO have been studied in mice, rats, dogs, and in human subjects. 30,[112][113][114][115][116] In humans, the absolute bioavailability of VO, determined after intravenous and oral administrations to the same volunteers, was high (up to 75%) and independent of food intake. 117 VO shows a linear, dose-proportional and timeindependent pharmacokinetics at doses from 2.5 mg to 75 mg. 118 It has an extensive volume of distribution as the plasma protein binding is 80-90%.…”
Section: Pharmacokineticsmentioning
confidence: 99%